Math, asked by ShahAshish7546, 1 year ago

Asec alpha - ctan alpha = d and bsec alpha + dtan alpha=d then

Answers

Answered by zen77
2
Hope this will help u..................
Attachments:
Answered by ishwarsinghdhaliwal
7

asec alpha - ctan alpha = d and bsec alpha - dtan alpha=c

 a \sec \alpha  - c \tan \alpha  = d \\ a \sec \alpha = d + c \tan \alpha \\ squaring \: on \: both \: sides  \\  {a}^{2}  \sec^{2}  \alpha  =  {d}^{2}  +  {c}^{2}tan^{2}  \alpha   \:  \:  \:  \:  \:  \:  \:  \: .....(1) \\ now \\ b \: sec \alpha  \:  - d \: tan \alpha  = c \\ b \: sec \alpha = c + d \: tan \alpha \\ squaring \: on \: both \: sides \:  \\{b}^{2} sec ^{2}  \alpha  =  {c}^{2}  +  {d}^{2} tan^{2} \alpha  \:  \:  \:  \: ...... (2) \\ adding \: (1) \: and \: (2) \\( {a}^{2}  +  {b}^{2} )sec ^{2}  \alpha  = ({c}^{2}  +  {d}^{2}) + ({c}^{2}  +  {d}^{2}) {tan}^{2}  \alpha \\( {a}^{2}  +  {b}^{2} )sec ^{2}  \alpha  = ({c}^{2}  +  {d}^{2})(1  + tan ^{2}  \alpha ) \\( {a}^{2}  +  {b}^{2} )sec ^{2}  \alpha  = ({c}^{2}  +  {d}^{2})(sec ^{2}  \alpha ) \\ {a}^{2}  +  {b}^{2} = {c}^{2}  +  {d}^{2} \\

Similar questions